Unique Supply Function Equilibrium with Capacity Constraints - Pär Holmberg (Uppsala University, Department of Economics, 2004)
Consider a market where producers submit supply functions to a procurement auction e.g. an electric power auction under uncertainty, before demand has been realized. In the Supply Function Equilibrium (SFE), every firm commits to the supply function maximizing his expected profit given the supply functions of the competitors. The presence of multiple equilibria is one basic weakness of SFE. This paper shows that with (i) symmetric producers, (ii) inelastic demand, (iii) a reservation price, and (iiii) capacity constraints that bind with a positive probability, there is a unique symmetric SFE.
Keywords: D43; D44; L11; L13; L94; 330; Supply function equilibrium; auction; oligopoly; capacity constraint; wholesale electricity market; Angebot; Kapazitätsauslastung; Elektrizität; Oligopol; Auktionstheorie